2008
DOI: 10.3310/hta12050
|View full text |Cite
|
Sign up to set email alerts
|

A multi-centre retrospective cohort study comparing the efficacy, safety and cost-effectiveness of hysterectomy and uterine artery embolisation for the treatment of symptomatic uterine fibroids. The HOPEFUL study

Abstract: The study results suggest that both UAE and hysterectomy are safe. No unexpected problems were detected following UAE after a long follow-up period (average 5 years). Complications are less common for UAE than hysterectomy. The cost-effectiveness analysis favours embolisation even after taking account of complications, expected side-effects associated with the procedure and subsequent re-treatments for women with a preference for uterus preservation. It is important to improve the management of expectations fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(94 citation statements)
references
References 2 publications
3
89
0
2
Order By: Relevance
“…However, a study of 397 women that retrospectively followed up women who had had either hysterectomy or UAE reported that 88% of women who had undergone hysterectomy felt that their symptoms were better and that 70% would recommend their treatment to a friend. 118 A disadvantage of this study was that the mean follow-up time was 8.6 years. By scrutinising the reference list of this study, we identified two similar studies.…”
Section: Hysterectomymentioning
confidence: 89%
See 2 more Smart Citations
“…However, a study of 397 women that retrospectively followed up women who had had either hysterectomy or UAE reported that 88% of women who had undergone hysterectomy felt that their symptoms were better and that 70% would recommend their treatment to a friend. 118 A disadvantage of this study was that the mean follow-up time was 8.6 years. By scrutinising the reference list of this study, we identified two similar studies.…”
Section: Hysterectomymentioning
confidence: 89%
“…54 In total, 17 women underwent hysterectomy and at 6 months 88% reported that they would have the same treatment again, suggesting that they were satisfied with the surgery. 54 After evaluating the data from these studies we decided to use 0.88 as our satisfaction level as this was reported in the large retrospective study 118 and supported by the smaller randomised study. 54 For the sensitivity analysis we used the proportion of women who would recommend their treatment to a friend from the two separate studies (0.70 and 0.93).…”
Section: Hysterectomymentioning
confidence: 99%
See 1 more Smart Citation
“…Embolising the uterine blood supply had been used earlier to manage post-partum haemorrhage and as treatment of uterine arterio-venous malformations, but it was the desire to reduce intraoperative haemorrhage at open myomectomy by Professor Jacques Ravina, which serendipitously led to the use of UAE as primary management of this common condition once it was realised that the embolisation lets to fibroid shrinkage and symptomatic improvement [1,2]. Many studies since have confirmed both the benefits and risks of UAE [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…terine artery embolization (UAE) has shown to be a valuable, minimally invasive alternative for the treatment of women with symptomatic leiomyomas, uterine vascular malformations, and postpartum hemorrhage (1)(2)(3)(4)(5)(6)(7)(8)(9). The procedure is performed with angiographic and fluoroscopic guidance.…”
mentioning
confidence: 99%